PENERAPAN LIBRARY TESSERACT OPTICAL CHARACTER RECOGNITION DALAM FITUR REIMBURSEMENT MENGGUNAKAN METODE KANBAN (Studi Kasus : PT. Kayana Nusa Teknologi) - Abdul Hakim; Samsoni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT. Kayana Nusa Teknologi is a technology development company. Currently, the company is still manually processing reimbursements, which is deemed to be less effective for a company. Innovation is needed to streamline this process and maximize the use of time to improve work processes within the company. In designing this application, the Kanban method is used, which provides a sequential or ordered approach to the software lifecycle, starting with analysis, design, coding, testing, and supporting stages. In addition, the use of Optical Character Recognition (OCR) technology is used, which can identify and convert text in image documents into text that can be read by computers. With the existence of this application, it is expected that the performance of employees will be more efficient, especially for Android users in the company.